Calculation of Pollution Indicators and Health Hazards of Heavy Elements in Surface Soils in Samarra City - Ibrahim, Shatha Amer; Abed, Mahmood Fadhil; Al-Tawash, Balsam Salim (Iraqi Journal of Science, 2018)
The current study focuses on the assessment of pollution indicators and health risks of heavy elements in the surface soil of Samarra City. Twelve soil sample collected from different sites in Samarra City, analysis of soil sample to find the heavy metals concentrations which As, Br, Co, Cr, Cu, Mn, Mo, Ni, Pb, Sn, V, Zn, Zr, U, B, Cd, Hg, Th, Ce, La, Th, B, Ba .The results are compared with limit of world standard (12). The higher values which refer to pollution in heavy metal are Cr, Cu, Ni, Zn, Zr, Cd due to industry activity and Hg higher concentration because of Pharmaceutical Industries and Medical Waste . The high concentration in V, Br, Mo, Se, As because of agriculture activity. The enrichment factor calculated for the purpose of calculating saturation coefficient and treatment, analysis and conversion of the values of raw concentrations and the creation of the local background of Iraq. The most of the results are less than five ,but few value are greater than five indicating the anthropogenic input of these elements in soil in Samarra City which are Co, Mo, U in S2 because of agriculture activity and using fertilizer. Mo , Sn in S2 because of highly building activity. Cu, Mo, Zn in S5 Because industrial and motor oil spill. Uranium in S2, S4 and S11 because military activity. Contamination factor (CF) and the value of the pollutant load index are less than 4 that’s mean sites are polluted medium to high. After applying the health risk assessment model, the risk value for each non-carcinogenic heavy element is found to be less than 4 and for all three exposure methods (ingestion, skin contact and inhalation), in terms of carcinogenic components, the average daily dose (LADD) ) And compared to slope coefficient (SF) collected from previous studies. Equations are applied to find less than 0.0001 which is indicative of the occurrence of cariogenic diseases that may affect people exposed to soil. The risk of soil or dust ingestion is more insecure in the area of ​​activity in the effect of cobalt and manganese than on adults, and chromium has an effect on adults at a high level. HI value of inhalation that’s effect on adults and children revel the most hazardous heavy elements is Mn, Cr, Co for adults and children. HI value of dermal absorption the most hazard element Cr, Hg , Ce for adults and children which exposed to the soil. Swallow soil effect on children and adults. Especially chromium and mercury, which in turn affect the health exposed to the ingestion of polluted soil.